Properties of Chitosan-Gelatine Based, Aloe Vera and Propolis Added Biofunctional Wound Dressing Material - Akkad, Haya; Çiftçi, Fatih; Erarslan, Azime; Özerol, Esma Ahlatcıoğlu (Taylor & Francis, 2026)
This study describes the development and characterization of a multilayered wound dressing composed of a chitosan (CHI), gelatin (GEL), and Aloe vera (AV) base layer integrated with electrospun polyvinyl alcohol (PVA)/propolis nanofibers (WD3). FE-SEM analysis showed a bead-free porous network with a mean fiber diameter of 185 ± 24 nm. XRD and DSC results confirmed the semi-crystalline structure and thermal stability of the scaffolds, with the WD1 baseline exhibiting a crystalline peak at 2θ = 26.070. Mechanical analysis demonstrated that the optimized WD3 formulation possesses a high dry tensile strength of ~49 MPa, which transitions into a highly conformable and flexible hydrogel state upon hydration, reaching a peak elongation at break of 68.4%. Swelling and degradation studies highlighted a superior fluid absorption capacity of 97% and a controlled mass loss of 18% over 7 hours, ensuring effective exudate management and structural longevity. Standardized LC-MS/MS fingerprinting of the propolis extract (TPC: 199.7 mg GAE/g) identified key polyphenols, including pinocembrin and galangin, which governed a sustained release profile following the Korsmeyer-Peppas model (n = 0.62). Biological assays confirmed that the WD3 group supported cell viability with a metabolic activity rate of 110.7% and provided antioxidant activity with an IC50 of 16.31 μg/mL. Furthermore, antibacterial tests showed an inhibition zone of 23.6 ± 2.1 mm against S. aureus. These results indicate that the multilayered CHI/GEL/AV/PVA/Propolis dressing provides the structural and biological properties necessary for potential applications in wound care.
Keywords: Wound Dressing; Burn Treatment; PVA; Chitosan; Aloe Vera; Propolis